PERSUASIVE SPEECH IN ISLAM AND LEARNING INDONESIAN - Ernaliana (LINGUISTIK MIKRO, MAKRO DAN SASTRA, 2025)
The researcher focuses on persuasion in Ustaz Maulana’s lecture. The problems studied in this study are (1) how is the form of persuasion in Ustaz Maulana’s Islamic lecture on the program “Islam Itu Indah” on Trans TV?, (2) how is the relationship between the form of persuasion in Ustaz Maulana’s Islamic lecture on the program “Islam Itu Indah” on Trans TV with Indonesian language learning in high school? So that this study does not become too broad and wide, the researcher limits the problem, namely, the researcher only takes two different themes broadcast in the same month and year, April 2014. In collecting data, the researcher uses the listening method, followed by the tapping technique. In addition, note-taking and recording techniques were used in this study. This study discusses how to analyze the form of persuasion in Ustadz Maulana’s lecture on the program Islam Itu Indah, including educational persuasion, propaganda persuasion, political persuasion, and advertising persuasion (advertisements). In the discussion, the research is also connected to Indonesian language learning in schools, especially at the level of high school grade XI odd semester on the competency standards of understanding speeches/greetings, lectures/sermons and conversations in interviews, namely lectures are used by teachers as visual media using LCD, besides that it can also be a source of learning for students